2016
DOI: 10.1038/srep37185
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Analysis of PAHs in Soils along an Urban–Suburban–Rural Gradient: scale effect, distribution patterns, diffusion and influencing factors

Abstract: Spatial statistical methods including Cokriging interpolation, Morans I analysis, and geographically weighted regression (GWR) were used for studying the spatial characteristics of polycyclic aromatic hydrocarbon (PAH) accumulation in urban, suburban, and rural soils of Beijing. The concentrations of PAHs decreased spatially as the level of urbanization decreased. Generally, PAHs in soil showed two spatial patterns on the regional scale: (1) regional baseline depositions with a radius of 16.5 km related to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 42 publications
(55 reference statements)
1
17
0
Order By: Relevance
“…Soil contamination with PAHs has been one of the most important environmental problems worldwide and requires an urgent solution [13][14][15]. At present, many places have been polluted with PAHs, such as Miami in the USA [16], Delhi in India [17], Beijing in China [18], Esbjerg in Denmark [19], Tyumen Oblast in Russia [20], and Ulsan in Korea [21,22], which, among others, have been studied by international researchers [23][24][25]. Nam et al [26] found that the average background PAH concentration in different soils worldwide followed the order Europe > North America > Asia >Oceania > Africa > South America.…”
Section: Introductionmentioning
confidence: 99%
“…Soil contamination with PAHs has been one of the most important environmental problems worldwide and requires an urgent solution [13][14][15]. At present, many places have been polluted with PAHs, such as Miami in the USA [16], Delhi in India [17], Beijing in China [18], Esbjerg in Denmark [19], Tyumen Oblast in Russia [20], and Ulsan in Korea [21,22], which, among others, have been studied by international researchers [23][24][25]. Nam et al [26] found that the average background PAH concentration in different soils worldwide followed the order Europe > North America > Asia >Oceania > Africa > South America.…”
Section: Introductionmentioning
confidence: 99%
“…Concerns over their chronic toxicity (mutagenicity and carcinogenicity), environmental persistence and ubiquitous presence in the environment have driven research interest into their sources and processing in the environment. 1,2 Most spatial distributions of PAHs in soils vary in scale and occur through diffuse pollution, [3][4][5][6] owing to the degree of remote economic development, population density, landscape, vegetation and land use. 7,8 This results in the contamination of large areas with hotspots having high PAH concentrations and is characterised by the absence of identiable point sources.…”
Section: Introductionmentioning
confidence: 99%
“…The land use types of the marginal areas of the city are mainly forest, grassland, and farmland. Such land use spatial pattern indicates that the areas within the Sixth Ring Road exhibit an obvious urbansuburban gradient (Peng et al 2016), and thus it is an ideal area for urbanization research.…”
Section: Study Areamentioning
confidence: 99%